MINIMUM WAGES, IMPORT STATUS, AND FIRMS' INNOVATION: THEORY AND EVIDENCE FROM CHINA. (5th August 2020) - Chu, Angus C.; Fan, Haichao; Furukawa, Yuichi; Kou, Zonglai; Liu, Xueyue
Abstract : This study explores the heterogeneous effects of minimum wage on innovation of different types of firms. We develop an open‐economy R&D‐based growth model and obtain the following result: raising the minimum wage reduces innovation of firms that use domestic inputs but increases innovation of firms that import foreign inputs. We test this result using city‐level data on minimum wages and firm‐level patent data in China. In accordance with our theory, we find that raising the minimum wage is associated with more innovation by importing firms and less by non‐importing firms. This result survives a battery of robustness checks. ( JEL E24, F43, O31)